2018
DOI: 10.1186/s12933-018-0803-z
|View full text |Cite
|
Sign up to set email alerts
|

Alogliptin prevents diastolic dysfunction and preserves left ventricular mitochondrial function in diabetic rabbits

Abstract: Background: There are increasing evidence that left ventricle diastolic dysfunction is the initial functional alteration in the diabetic myocardium. In this study, we hypothesized that alogliptin prevents diastolic dysfunction and preserves left ventricular mitochondrial function and structure in diabetic rabbits. Methods: A total of 30 rabbits were randomized into control group (CON, n = 10), alloxan-induced diabetic group (DM, n = 10) and alogliptin-treated (12.5 mg/kd/day for 12 weeks) diabetic group (DM-A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 54 publications
2
24
0
1
Order By: Relevance
“…Although the pathogenesis of DCM is not completely understood, emerging evidence demonstrate that mitochondrial dysfunction plays an essential role in the development of DCM [2,3]. Zhang X et al recently reported that treatment of diabetic rabbits with dipeptidyl peptidase-4 inhibitor could prevent cardiac dysfunction, either preserve myocardial mitochondrial function or improve mitochondrial biosynthesis [31]. The present study demonstrated the suppressed mitochondrial biogenesis, impaired mitochondrial function, and increased oxidative stress in the myocardium of T2DM rats.…”
Section: Discussionsupporting
confidence: 64%
“…Although the pathogenesis of DCM is not completely understood, emerging evidence demonstrate that mitochondrial dysfunction plays an essential role in the development of DCM [2,3]. Zhang X et al recently reported that treatment of diabetic rabbits with dipeptidyl peptidase-4 inhibitor could prevent cardiac dysfunction, either preserve myocardial mitochondrial function or improve mitochondrial biosynthesis [31]. The present study demonstrated the suppressed mitochondrial biogenesis, impaired mitochondrial function, and increased oxidative stress in the myocardium of T2DM rats.…”
Section: Discussionsupporting
confidence: 64%
“…Accumulated basic and clinical evidence have demonstrated that DPP4 dose-dependently increased oxidative stress production (Ishibashi et al, 2013; Zheng et al, 2015b). More importantly, previous studies have proved that DPP4 inhibitors, such as Alogliptin or Vildagliptin, suppressed oxidative stress in different animal models (Abdelsalam and Safar, 2015; Yisireyili et al, 2016; Aroor et al, 2017; Zhang et al, 2018). With regard to the association between oxidative stress and BDNF, oxidative stress has been proven to cause a decrease in BDNF expression in basic research, while the underlying mechanisms was partly attributed to the impairment of N-methyl- D -aspartate channel (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Mitoquinone (MitoQ), a mitochondrial-targeted antioxidant, could inhibit fibrosis in pressure overloaded hearts via targeting mitochondrial ROS-mediated signaling TGF-β1, NADPH oxidase 4 (NOX4), and Nrf2 pathway 47 . Bendavia and alogliptin could improve mitochondrial dysfunction, relieved cardiac fibrosis by improving mitochondrial biogenesis 48,49 .…”
Section: Mitochondrial Dysfunction In Cardiac Fibrosismentioning
confidence: 99%
“…Mitochondrial membrane potential and membrane structural damage are also important characteristics in cardiac fibrosis. It is reported that alogliptin alleviated interstitial fibrosis in diabetic rabbits by reducing the production of mitochondrial ROS, preventing the mitochondrial membrane depolarization, and improving the swelling of mitochondria 49 . Similarly, melatonin and ephedrine-4 could alleviate oxidative stress and cardiac fibrosis through maintaining the integrity of mitochondrial membrane and preventing the release of cytochrome C 53 .…”
Section: Mitochondrial Dysfunction In Cardiac Fibrosismentioning
confidence: 99%
See 1 more Smart Citation